PENGARUH BLACK CARBON DAN SULFUR TERHADAP KOEFISIEN GRIP BAHAN BAN DENGAN BATIKAN SILANG PADA KONDISI LINTASAN BETON KERING DAN BASAH - FERI IRAWAN, WILDAN, Ir. Pramuko Ilmu Purbo Putro, MT, Muh. Alfatih Hendrawan., ST., MT (2016)
This study aims to determine the effect of black carbon and sulfur to the coefficient of grip the tire material parttern concrete cross on the track wet and dry. Tired works by utilizing the frictional force between the surface of the tire with the road surface friction force is also called as a grip. Grip can be enhanced by improving the coefficient of friction between the tire to the road, because the road is a constant magnitude that can not be changed then to fix the coefficient friction by improving the quality of tire compound. Material for the tire compound used in the form of natural rubber and synthetic rubber SBR RSS mixed with carbon black, sulfur, white oil, ZnO, stearic acid, paraffin wax, MBTS, coumarone resin. The materials are mixed using mixing roll machine, the result of mixing a sheet of compound. Compound pressed to 1300C temperature for 30 minutes to reach kematang This process is also called vulcanization, the results of the test specimen prosesini form. Tensile test using a rubber testing equipment with ISO standards. Hardness testing using a shore hardness tester with ISO standards. Testing the coefficient of grip with a load of 16.2 kg using tool with the principle of equality of power is known, the addition of black carbon and sulfur influence coefficient of grip. Increasingly the provision of black carbon and sulfur tire grip coefficient decreases.